AIDS Counselling Services in an Anonymous Clinic, Nakhon Sri Thammarat - Ruttarasarn, Saowaros (Journal of Health Science of Thailand, 1993)
Since August 1991, the Office of Communicable Disease Control Region 11, Nakhon Sri Thammarat, has operates an anonymous counseling clinic at the regional TB Centre. There were 1,948 attendants receiving the counseling services up to September 1993. In addition, 610 cases had accessed the services be telephone. The reasons for gaining high popularity were (1) a good location, (2) a well-trained counselor providing services, and (3) effective advertising activities. The outcomes and impacts of the clinic activities included (1) serving many people on AIDS counseling, (2) gaining more experience in operating an anonymous clinic, (3) learning of social characteristics of people at risk of HIV infection, and (4) an appropriate training site on anonymous counseling services for provincial health officers in the region.